Hubungan Kecerdasan Emosi Antara Ibu dengan Anak Usia Dini di Masa Pandemik Covid-19 - Kurniawaty, Yuni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: to identify the relationship of emotional intelligence between mothers and early childhood during the covid-19 pandemicMethods: This article of research was correlation with cross sectional design. The research was carried out in the Catholic Santa Katarina Kindergarten, Jalan Mojopahit No. 38 Surabaya. The study population of parents of guardians of students of TK B Katarina used total sampling. Research sample of 30 respondents. The independent variable of maternal emotional intelligence used the Trait Emotional Intelligence Questionnaire-Short Form (TEIQue-SF) questionnaire. The dependent variable of children's emotional intelligence using the Strengths and Difficulties Questionnaire - Parent Reports (SDQ-PR) questionnaire.Results: The results show that most of the emotional intelligence of mothers was low as much as 86% of respondents. Emotional intelligence of children more than 50% was classified as abnormal or abnormal 56.7% of respondents. Spearman Rank Test p = 0.094 means p > α means that there is no emotional intelligence relationship between mothers and early childhood during the covid-19 pandemic.Conclusion: There is no emotional intelligence relationship between mothers and early childhood during the covid-19 pandemic. It was recommended in further research to examine other factors that were more dominant that have an association with emotional intelligence of early childhood.